WHEAT BRAN EXTRACT MIMICS STATIN LIKE ACTION IN HYPERLIPIDEMIC RABBITS: AN EXPERIMENTAL STUDY - Chadha, Rashi; Purohit, Ashok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The study was aimed to evaluate the hypolipidemic and antioxidant effect of Triticum aestivum (wheat) bran extraction cholesterol-fed rabbits. Methods: The induced hyperlipidemic rabbits were treated with 70% ethanolic extract of wheat bran at a dose of 500 mg/kg body weight/day. The experimental protocol was designed for control, hyperlipidemic, wheat bran extract, and statin-treated groups for 60 days. The estimations for serum lipid profile, lipid peroxidation (LPO), and ferric reducing ability of plasma (FRAP) were done, and histopathological study of thoracic aorta was carried out. Results: Oral administration of wheat bran extract caused significant reductions in the serum lipid profile by 94.30% (total cholesterol), 96.73% (low-density lipoprotein cholesterol), and 58.28% (triglycerides). It significantly decreased the LPO and enhanced the antioxidant capacity (FRAP) activity as compared to the hyperlipidemic rabbits. Histopathology revealed that wheat bran extract treatment prevented the accumulation of cholesterol and regressed atheromatous plaques significantly in the aorta as compared to the hyperlipidemic group, and the results were comparable to that of the standard drug statin. Conclusion: The study exhibited that wheat bran extract controls atherosclerosis just like statin and can be used as a regular dietary supplement to manage cholesterol levels and prevent cardiovascular problems.